2017
DOI: 10.1098/rsob.170149
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophilaCsrA regulates a metabolic switch from amino acid to glycerolipid metabolism

Abstract: Legionella pneumophila CsrA plays a crucial role in the life-stage-specific expression of virulence phenotypes and metabolic activity. However, its exact role is only partly known. To elucidate how CsrA impacts L. pneumophila metabolism we analysed the CsrA depended regulation of metabolic functions by comparative 13C-isotopologue profiling and oxygen consumption experiments of a L. pneumophila wild-type (wt) strain and its isogenic csrA− mutant. We show that a csrA− mutant has significantly lower respiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…Indeed, using 13 C-isotopologue profiling and carbon-flux analyses of a wild-type and a csrA mutant strain confirmed that CsrA plays a major role in regulating the carbon flux between the PPP and the glycolysis (Häuslein et al, 2017 ). Furthermore, this study highlighted the impact of CsrA on the bipartite metabolism of L. pneumophila , as the absence of CsrA induces a reduction of the carbon flux from serine via gluconeogenesis into the PPP.…”
Section: Cross Talk Between Metabolism and The Stringent Responsementioning
confidence: 92%
See 4 more Smart Citations
“…Indeed, using 13 C-isotopologue profiling and carbon-flux analyses of a wild-type and a csrA mutant strain confirmed that CsrA plays a major role in regulating the carbon flux between the PPP and the glycolysis (Häuslein et al, 2017 ). Furthermore, this study highlighted the impact of CsrA on the bipartite metabolism of L. pneumophila , as the absence of CsrA induces a reduction of the carbon flux from serine via gluconeogenesis into the PPP.…”
Section: Cross Talk Between Metabolism and The Stringent Responsementioning
confidence: 92%
“…Similar to glucose, the carbon from glycerol is mainly shuffled into gluconeogenesis and PPP for histidine and mannose production, but only low flux rates of carbon from glycerol into the TCA cycle were reported (Häuslein et al, 2016 ). In contrast, saturated lipids like palmitate, another carbon source shown to be predominantly used after amino acid depletion, is used for energy production and PHB synthesis (Häuslein et al, 2017 ). Taken together, the results from 13 C- isotopologue profiling and flux analyses suggested that the life cycle switch of Legionella is also reflected by a metabolic shift from amino acids usage during replication to glycerolipids and glucose when entering transmissive phase (Häuslein et al, 2017 ; Figure 2 ).…”
Section: The Biphasic Life Cycle Of L Pneumophilamentioning
confidence: 99%
See 3 more Smart Citations